2011
DOI: 10.1002/lary.21841
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on postoperative pulmonary humidification after total laryngectomy: External humidifier versus heat and moisture exchanger

Abstract: This RCT clearly shows the benefits of immediate postoperative airway humidification by means of an HME over the use of an EH after TLE. This study therefore underlines that HMEs presently can be considered the better option for early postoperative airway humidification after TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 22 publications
4
60
0
2
Order By: Relevance
“…excessive sputum production and involuntary coughing). Sleep disturbance is prevalent in these patients [2, 3]. The respiratory problems and poor sleep quality leads to low patients’ satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…excessive sputum production and involuntary coughing). Sleep disturbance is prevalent in these patients [2, 3]. The respiratory problems and poor sleep quality leads to low patients’ satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the world and specifically in South Africa, HMEs are not affordable. Annual costs for HMEs conservatively range from the equivalent of U.S. $350 to U.S. $1750 . Consequently, reliance is placed on simpler and inexpensive solutions to improve tracheal climate in patients with laryngectomies.…”
Section: Introductionmentioning
confidence: 99%
“…17 A more recent study in laryngectomized adult patients found better cough and adherence to HME than to HH in the immediate postoperative period. 18 The humidifier in that study did not use heated tubing, which may have resulted in condensate, potentially affecting outcomes. In the long-term study we also documented significantly fewer lower-respiratory-tract infections, acute respiratory admissions, tracheostomy tube occlusions/emergency changes, and treatment failures during the HH period.…”
Section: Discussionmentioning
confidence: 94%